1979
DOI: 10.1107/s0567740879002442
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen bonds in Schlippe's salt: refinement of the crystal structures of Na3SbS4.9H2O by X-ray diffraction and Na3SbS4.9D2O by neutron diffraction at room temperature

Abstract: which is probably Zr, the average number of short bonds is three. Zachariasen (1973) has discussed the radii of Pu and other actinide elements in their various phases and deduced the number of valence electrons. He defines the radius as r = Vial3/25/6 where V a is the mean atomic volume. For the present material V a = 22.42 A 3, r = 1.583 A and the mean valence is therefore 5.2 electrons. This value is the same as that of 7-Pu. AbstractThe room-temperature crystal structure of Schlippe's salt, space group P2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
23
0
1

Year Published

1981
1981
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 5 publications
(6 reference statements)
4
23
0
1
Order By: Relevance
“…The dimensions of the NCS group agree well with those previously found in N-bonded thiocyanate complexes (Norbury, 1975). The two independent water molecules of the structure (Mereiter, Preisinger & Guth, 1979). Two O-H...S bonds similar in lengths to those of the title compound have been found by neutron diffraction in Mg2S203.6H20 (O...S = 3.26 and 3.25 A, H. • • S = 2.28 and 2.34/k; Elerman, Fuess & Joswig, 1982).…”
supporting
confidence: 86%
“…The dimensions of the NCS group agree well with those previously found in N-bonded thiocyanate complexes (Norbury, 1975). The two independent water molecules of the structure (Mereiter, Preisinger & Guth, 1979). Two O-H...S bonds similar in lengths to those of the title compound have been found by neutron diffraction in Mg2S203.6H20 (O...S = 3.26 and 3.25 A, H. • • S = 2.28 and 2.34/k; Elerman, Fuess & Joswig, 1982).…”
supporting
confidence: 86%
“…The ten shortest of these are in the range O-S = 3.2-3.5 A. Their mean value of 3.38 (8) A compares well with the O-S distance of 3.33 A for the 'average' O-H...S bond (Mereiter, Preisinger & Guth, 1979) or the 3.377(2)A O-H...S bond known from neutron diffraction of K2[Co(NCS)4].H20.2CH3NO 2 (Wood & McMullan, 1984). While three of the water molecules in the title compound show relatively weak interactions (O-S = 3.5-3.9 A), there is no suitable second Hbond acceptor available for 0(7).…”
supporting
confidence: 53%
“…The O... S distance is slightly longer than the 3.180 (7) and 3.199 (6)A determined for the two intermolecular hydrogen bonds in HTBM. However, the OH...S hydrogen bonds in these two compounds are among the shortest bonds of this class so far observed (Mereiter et al, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…Hydrogen bonds of this type are not well documented. The few examples of neutron diffraction studies found in the literature all refer to © 1981 International Union of Crystallography inorganic complexes where the water of hydration forms hydrogen bonds with S ligands (Mereiter, Preisinger & Guth, 1979). The neutron diffraction data were collected at 20 K to reduce the amplitude of the thermal motion from the large values observed in the room-temperature X-ray structure.…”
Section: Introductionmentioning
confidence: 99%